Marketing the Tourism Potentials of Owo Community for the Development of Ondo State, Nigeria (2012)
The aim of this study is to identify the tourism potentials in Owo Community and their contribution to the socioeconomic development of the people. The study made use of purposive sampling method. Systematic random sampling was used to administer questionnaires at interval of 10lh respondents targeted at house hold heads. The results show that the level of patronage of tourism potentials in Owo is relatively high as revealed by the data collected. The impacts of tourism potentials in the study area included boosting of income, employment and business. The study concludes that tourism potentials in Owo community has high patronage and has positive impact on people’s socio-economic lives, but there are many challenges facing the sector in the study area. Some of which are lack of accommodation, lack of awareness, inadequate water supply, lack of support by both Local and State governments for both Igogo and Ero festivals. The study recommends proper funding of Owo Museum by the federal government as well as appropriate packaging and marketing of Igogo and Ero festivals to meet international standards among other recommendations.